A rare case of multiple dental anomalies in non syndromic patient (Bangladesh Journal of Medical Science, 2013)
Human dental anomalies are formative defects to variety of genetic and environmental factors. Multiple anomalies are seen in patient with chromosomal abnormalities or specific syndromes. Multiple odontogenic anomalies in non syndromic patient are unusual and rare. This paper reports a rare, unique and interesting case of multiple odontogenic anomalies such as bilateral macrodontia of maxillary central incisor, hypodontia, hyperdontia in lower anterior mandible, transposition in left anterior maxilla and taurodontism with molars in a single non syndromic young Indian female patient. Patients with multiple dental anomalies require multidisplinary treatment approaches such as surgical, orthodontic, endodontic, prosthodontic rehabilitation etc. Multiple dental anomalies in non syndromic patient are rare and needs early diagnosis and require multidisplinary approach. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17444 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 95-98